PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI DALAM MENINGKATKAN INTENSI BERWIRAUSAHA MAHASISWA - Yeni Rokhilawati; Arif Efendi (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
There is an increase in entrepreneurial intensity among students who are members of HIPMI PT IAI Ibrahimy Genteng, while there are also students who, even though they do not yet have strong intentions, are still committed to the organization. This makes researchers interested in conducting this research. This research aims to determine the influence of organizational culture and organizational commitment in increasing the entrepreneurial intentions of students who are members of HIPMI PT IAI Ibrahimy Genteng. This type of research is associative with a quantitative research approach. Data collection techniques use participant observation techniques, questionnaires and documentation. Based on the results of the T Test research on Organizational Culture Variables, it is known that tcount equal to 0.412< t table 2,000 and a significance value of 0.681> 0.05, indicating that partially the organizational culture variable (X1) has a positive and insignificant effect on entrepreneurial intentions (Y). Meanwhile, the results of the T Test Research on the Organizational Commitment Variable were found to be t count amounting to 5,057 > t table 2,000 and the Sig value. 0.000 < 0.05, indicating that the Organizational Commitment variable has a positive and significant effect on entrepreneurial intentions (Y). Based on the results of the F test, it is known that the unstandardized coefficient (B) value of the Organizational Culture variable has a positive value of 0.041 or 4.1% and a significance value of 0.000 <0.05. Meanwhile, the unstandardized coefficient (B) value of the Organizational Commitment variable has a positive value of 0.408 or 40.8% and a significance value of 0.000 <0.05. Simultaneously, the variables organizational culture (X1) and organizational commitment (X2) simultaneously or jointly influence the entrepreneurial intentions (Y) of HIPMI PT IAI Ibrahimy Genteng members.